2015
DOI: 10.1186/s12944-015-0142-y
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of krill oil with high phospholipid content increases sum of EPA and DHA in erythrocytes compared with low phospholipid krill oil

Abstract: Background: Bioavailability of krill oil has been suggested to be higher than fish oil as much of the EPA and DHA in krill oil are bound to phospholipids (PL). Hence, PL content in krill oil might play an important role in incorporation of n-3 PUFA into the RBC, conferring properties that render it effective in reducing cardiovascular disease (CVD) risk. The objective of the present trial was to test the effect of different amounts of PL in krill oil on the bioavailability of EPA and DHA, assessed as the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Furthermore, the inclusion of omega-3 fatty acids in prenatal vitamins is not standard, despite being identified as an important nutrient in pregnant women [22,23]. Furthermore, there is precedence for the need for sufficient omega-3 fatty acid intake both prior to and during pregnancy; numerous studies have investigated the bioavailability and incorporation kinetics of omega-3 fatty acids in serum, red blood cell lipid membranes, and various tissues [49,50,51,52,53]. Tissue uptake kinetics indicate EPA half-maximal levels in blood rise rapidly (3–5 days) and reach half-maximal red blood cell membrane incorporation in one month [49], but DHA incorporation kinetics are slower and more erratic [49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the inclusion of omega-3 fatty acids in prenatal vitamins is not standard, despite being identified as an important nutrient in pregnant women [22,23]. Furthermore, there is precedence for the need for sufficient omega-3 fatty acid intake both prior to and during pregnancy; numerous studies have investigated the bioavailability and incorporation kinetics of omega-3 fatty acids in serum, red blood cell lipid membranes, and various tissues [49,50,51,52,53]. Tissue uptake kinetics indicate EPA half-maximal levels in blood rise rapidly (3–5 days) and reach half-maximal red blood cell membrane incorporation in one month [49], but DHA incorporation kinetics are slower and more erratic [49].…”
Section: Discussionmentioning
confidence: 99%
“…triglycerides and phospholipids, since the digestion of fat in the gastrointestinal tract is tailor-made for optimal absorbtion of this type of nutrients [23]. It is of note, however, that Ramprasath and coworkers have published their observation that the content of phospholipids in krill oil may have an impact on the bioavailability of the omega-3 FAs [24]. Given that the preparation tested in our study was highly purified with a phospholipid content of >98%, this may have led to a higher increase in the omega-3 index than would a normal krill-oil preparation with an approximately 40% phospholipid content, provided comparable doses of omega-3 FAs.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained data on lipid class composition and content mean that when such fish is consumed, nearly or more than half of the essential n-3 LC-PUFA comes as TAG form. Recent studies showed that bioavailability of FA, including LC-PUFA esterified as TAG may be lower than that esterified as PL [58,59], but see [60]. Thus, distribution of LC-PUFA in major lipid classes should be further addressed in studies of nutritional quality of various fish products.…”
Section: Content Of Essential Lc-pufa In Fish Pl and Tagmentioning
confidence: 99%